2019
DOI: 10.25518/1780-4507.18211
|View full text |Cite
|
Sign up to set email alerts
|

A review of Tuta absoluta (Lepidoptera: Gelechiidae) host plants and their impact on management strategies

Abstract: Introduction. Tuta absoluta is one of the most harmful insect pests of tomato crops worldwide. While its host plants mainly include Solanaceae species, recent studies suggest that it can lay eggs and develop on a wider range of wild and cultivated plants. No complete list of host plants based on available scientific data exists. Such information is important for those who aim at performing integrated management strategies against this pest, especially when it comes to identify host reservoirs where the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Although researchers and the government have attempted to limit the spread of T. absoluta in China by working together, the pest was found in the Xinjiang region of China in 2017 (Zhang et al, 2020 ). In 2018, the damage of this pest has also been reported in protected-field fresh marketing tomatoes in Lincang, Yunnan province (Cherif and Verheggen, 2019 ; Zhang et al, 2020 ). Recent studies have found that T. absoluta is spreading at 800 km each year (Cherif and Verheggen, 2019 ; Li Xiaowei, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although researchers and the government have attempted to limit the spread of T. absoluta in China by working together, the pest was found in the Xinjiang region of China in 2017 (Zhang et al, 2020 ). In 2018, the damage of this pest has also been reported in protected-field fresh marketing tomatoes in Lincang, Yunnan province (Cherif and Verheggen, 2019 ; Zhang et al, 2020 ). Recent studies have found that T. absoluta is spreading at 800 km each year (Cherif and Verheggen, 2019 ; Li Xiaowei, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…In 2018, the damage of this pest has also been reported in protected-field fresh marketing tomatoes in Lincang, Yunnan province (Cherif and Verheggen, 2019 ; Zhang et al, 2020 ). Recent studies have found that T. absoluta is spreading at 800 km each year (Cherif and Verheggen, 2019 ; Li Xiaowei, 2019 ). In the light of these new findings, specifically in terms of migratory patterns, a more focused tracking of tomato-growing areas is necessary throughout China; otherwise, tomatoes elsewhere in the country will lose their resistance to the pest.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations